(untitled) (Stavební obzor - Civil Engineering Journal, 2024)
With the increasing intensity of evapotranspiration caused by the changing climate, there is a growing need for water. This is especially true in locations where water-intensive vegetables are grown in intensive agriculture. Historically, irrigation systems were built in many intensive agriculture areas in Czechia, but they fell out of use, and evidence of their location was lost. However, Water Management Maps, which were only issued in paper form and have never been fully digitized, can provide evidence about the location of these large-scale irrigation systems. In this paper, we present a method for digitizing irrigation systems using the segmentation and classification of individual segments in the ArcGIS environment. The resulting raster is converted to polygons and is blended with the Land Parcel Identification System layer, resulting in a layer of irrigated land. Two statistical analyses were performed on this layer: statistics of the areas corresponding to the individual source watercourses, and statistics of the type of source.